Alien Pulse Rejection in Concurrent Firing LIDAR - Gunzung Kim; Jeongsook Eom; Yongwan Park (Remote Sensing, 2022)
Mobile pulse light detection and ranging (LIDAR) is an essential component of autonomous vehicles. The obstacle detection function of autonomous vehicles requires very low failure rates. With an increasing number of autonomous vehicles equipped with LIDAR sensors for use in the detection and avoidance of obstacles and for safe navigation through the environment, the probability of mutual interference becomes an important issue. The reception of foreign laser pulses can lead to problems such as ghost targets or a reduced signal-to-noise ratio (SNR). In this paper, we presented the probability that any LIDAR sensor would interfere mutually by considering spatial and temporal overlaps. We presented some typical mutual interference scenarios in real-world vehicle applications, as well as an analysis of the interference mechanism. We proposed a new multi-plane LIDAR sensor which used coded pulse streams encoded by carrier-hopping prime code (CHPC) technology to measure surrounding perimeters without mutual interference. These encoded pulses utilized a random azimuth identification and checksum with random spreading code. We modeled the entirety of the LIDAR sensor operation in Synopsys OptSim and represented the alien pulse elimination functionality obtained via modeling and simulation.